Host Feeding Patterns of Mansonia (Diptera, Culicidae) in Rural Settlements near Porto Velho, State of Rondonia, Brazil - Alonso, Diego Peres [UNESP]; Amorim, Jandui Almeida; de Oliveira, Tatiane Marques Porangaba; de Sá, Ivy Luizi Rodrigues; Possebon, Fábio Sossai [UNESP]; de Carvalho, Dario Pires; Ribeiro, Kaio Augusto Nabas; Ribolla, Paulo Eduardo Martins [UNESP]; Sallum, Maria Anice Mureb (MDPI, 2023)
Mosquito females of the genus Mansonia (Blanchard) can be a nuisance to humans and animals since they are voraciously hematophagous and feed on the blood of a variety of vertebrates. Despite their relevance, there is a lack of investigation into the blood-feeding patterns of the Mansonia species. Knowledge of the host preference is crucial in establishing the public health importance of a mosquito species and its potential to be involved in the transmission dynamics of pathogens. Species that are primarily anthropophilic can be more effective in spreading vector-borne pathogens to humans. In this study, we used an Illumina Nextera sequencing protocol and the QIIME2 workflow to assess the diversity of DNA sequences extracted in the ingested blood of mosquito species to evaluate the overall and local host choices for three species: Ma. titillans, Ma. Amazonensis, and Ma. humeralis, in rural areas alongside the Madeira River in the vicinities of the Santo Antonio Energia (SAE) reservoir in the municipality of Porto Velho, Rondônia, Western Brazil. By performing our analysis pipeline, we have found that host diversity per collection site showed a significant heterogeneity across the sample sites. In addition, in rural areas, Ma. amazonensis present a high affinity for B. taurus, Ma. humeralis shows an overall preference for C. familiaris and B. taurus, but also H. sapiens and E. caballus in urban areas, and Ma. titillans showed more opportunistic behavior in rural areas, feeding on wild animals and G. gallus, though with an overall preference for H. sapiens.
Keywords: biting activity; blood source; Mansoniaspp; NGS